Etuaptmumk (Two-Eyed Seeing) and Ethical Space: Ways to Disrupt Health Researchers' Colonial Attraction to a Singular Biomedical Worldview - Moneca Sinclaire; Annette Schultz; Janice Linton; Elizabeth McGibbon (York University Libraries, 2021)
Indigenous research on Turtle Island has existed for millennia, where knowledge(s) to work with the land and its inhabitants are available for next generations. These knowledge systems exist today but are rarely viewed as valid biomedical 'facts' and so are silenced. When Indigenous knowledge is solicited within health research, the knowledge system is predominantly an 'add-on' or is assimilated into Western understandings. We discuss disrupting this colonial state for nurse researchers. Two concepts rooted in Indigenous teachings and knowledges, Etuaptmumk (Two-Eyed Seeing) and Ethical Space, shed light on ways to disrupt health researchers' attraction to a singular worldview which continue to privilege Western perspectives. Knowledge rooted in diverse knowledge systems is required to challenge colonial relations in health research and practice. A synergy between Etuaptmumk and Ethical Space can support working with both Indigenous and biomedical knowledge systems in health research and enhance reconciliation.